Context and process challenges associated with supervising postgraduate dissertations: An example from marketing. Issue 1 (March 2019) - Vos, Lynn; Armstrong, Kate
Abstract: This article reports the findings of a study into the challenges that U.K. marketing academics face in supervising postgraduate dissertations. Findings from semi-structured interviews with supervisors from 10 UK Universities are categorised using elements of Biggs' (1989) 3P and Astin's (1970) I-E-O conceptual frameworks of teaching and learning. In particular, the study looks at the challenges that supervisors perceive with the dissertation process and whether they are context dependent (related to student characteristics or situational/institutional factors) or process dependent -- related to dissertation procedural factors and supervisor-student transactional and relational factors. The main objective is to assess which challenges are more amenable to solutions or mitigation, at least in the short term. In addition, the findings are compared with the literature to identify if there are commonalities or unique differences between those who supervise marketing dissertations and those from other disciplines and to suggest solutions. While institutional factors such as the drive to recruit more high-fee paying international students and the policy of keeping the master's degree to one year may be difficult to change in the short run, there are many other opportunities to improve the dissertation experience for both supervisors and students. Highlights: Biggs' (1993) 3P and Astin's (1970) I-E-O conceptual frameworks of teaching and learning have been used to investigate and categorise challenges faced by UK PG dissertation supervisors. Semi-structured interviews were carried out with supervisors from ten different UK Universities and the challenges were identified as being either context dependent or process dependent. The findings are compared with the literature to determine commonalities or unique differences between those who supervise marketing dissertations and those from other disciplines. Recommendations are also provided.